Accession of CIS countries to the World Trade Organisation - Matthias Lücke (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
This paper discusses the benefits as well as the adjustment problems resulting from the proposed accession of the member countries of the Commonwealth of Independent States (CIS) to the World Trade Organisation (WTO). In the area of trade-related policies, the CIS countries will have to make strategic decisions on policy objectives that have so far been avoided. Necessary adjustments to specific policy instruments will be limited and mostly technical in nature. Similarly, current plans for regional integration among CIS countries are fundamentally in compliance with WTO rules. However, negotiating strategies should be carefully coordinated among CIS countries that are in a de facto, though not necessarily a de jure customs union. Systemic transformation, especially the imposition and further strengthening of financial discipline on formerly socialist enterprises through privatization and elimination of subsidies, will need to be carried forward vigorously. Benefits of WTO accession include the consolidation of recent improvements in market access and, above all else, greater credibility for market-oriented reform policies through the international commitments to be entered into by CIS governments with respect to future trade-related policies.
Keywords: F02; 330; Außenwirtschaftspolitik; Außenhandelsliberalisierung; Übergangswirtschaft; WTO-Regeln; Handelsregionalismus; GUS-Staaten; Welt